Against the In-difference of Economical Objects. A Look form the utrumque ius (Nueva Granada, 18th and 19th Century) - Cellurale, Mariateresa (2019)
The treatment of the relicta pia (pious bequests assigning temporal goods to the purpose of salvation of the soul) in Nueva Granada in the eighteenth and nineteenth century, where properly studied according to its own dogmatic (a juridical one, originated in the Western canon of Roman descent), provides the opportunity to rethink the idea of secularization itself, as a form of transmission of material, juridical and political resources (land, iurisdictio), along the transition from the ancien régime to constitutional and legalist republics. The notion of «spiritual» or «spiritualized» goods, placed outside the commercium, among which land must be possibly included, as object of pious dispositions, refers to sacrum, the sacred, as an «antineutral» dimension of politics, law and justice; this dimension originates in the pignora of the pagan religio, a pactist and communitarian one, and lingers on in Christian relicta and relics, described and interpreted according to the set of concepts, principles and institutions of the ius commune, Roman and canonical, plural and casuistical; a system far from all blunt identification with the «law of the Catholic Monarchy», and whose rule continues for decades after the establishment of Republics in Hispanic America. In its effort to create modern «property», Bourbon laws intervene against customary and immaterial forms of gaining and circulating rights on land, neutralizing dispositives of the ancient sacrum, so announcing the transition of law to an abstract dimension, tending to depoliticization, due to legalism and positivism. The liberal State rising triumphant from the revolutions will eventually displace politics, previously established in rendering justice, to new territories, temporarily coextensive with the domains of (political) economy.